The Influence of Hedonistic Motives, Fashion Interest, and Positive Emotions on the Impulsive Buying of Fashion Products with Sales Promotion as Moderating Variables - Utami, Yekti; Kendaga, Jasmine Azhari Findra; Diantoro, Aris Kusumo; Kusmantini, Titik (International Journal of Applied Business and International Management, 2021)
This study analyzes the effect of hedonic motives, fashion involvement, and positive emotions on impulsive buying of fashion products with sales promotion as a moderating variable. This quantitative study used the accidental sampling method. The sample was 122 respondents. Analysis techniques were used based on Partial Least Square (PLS) to test the hypotheses. The results indicate that 1) hedonic motives, fashion involvement, and positive emotions have a positive and significant effect on impulsive buying fashion products, 2) sales promotion, sales promotion, and sales promotion can strengthen the influence of positive and significant positive emotions on the impulsive buying of fashion products.